(untitled) (The Research of Medical Science Review, 2025)
Background: Genetic variability in HIV-1 poses significant obstacles to treatment efficacy, particularly in regions like Lahore, Pakistan. This study aimed to characterize genetic diversity in HIV-1 pol gene among high-risk groups in Lahore. Methodology: Thirty-five plasma samples were collected. After viral RNA extraction, pol gene amplification was done using thermocycler. Sanger sequencing was done to detect genetic variability involved in drug resistance. Bioinformatics analysis was performed to build phylogenetic tree and to do assessment of drug resistance in protease (PR), integrase (IN) and reverse transcriptase (RT) regions of HIV-1 pol gene. Results: There were genetic similarities with HIV-1 separates from Pakistan and South Africa. Phylogenetic analysis classified sequences into sub-subtypes 02_AG, subtype A, and subtype G. Subtype 02_AG predominated, representing 44% prevalence in Lahore. We found significant substitutions along PR regions at 113V, K14R, L19P, K20I, N37D, L63S, H69K, M36I, L89M. Resistance mutations to nucleoside reverse transcriptase inhibitor (NRTI) at regions S68G, D67DN and V75VM were found. Regarding non-nucleoside-analog-reverse-transcriptase-inhibitors, resistance was found at E138A and V106I. Other substitutions that were detected through complete length of RT area were K32Q, V35T, E36I, K49R, I135V, D123E, S162A, T165I, Q174K, D177E, K173T, I178L, T200A, Q207E, P243A, V245Q, R356K, S322T, E291D, P294T, A272P, T286A, V292I, I293V, I326V, G335D, M357R, G359S, K366Q, T369A, E370G, A371V, I375V, T377I, K390S, K395R, A400T, T403M, E432D, R461K, D471E, K476R,Q480H, H483Y, K512R, L491S, L517I, S519N, Q524K, K527E, A534S , A554N, E529D.There was only one E157Q mutation in the Integrase strand transfer inhibitors (INSTI) accessory region. Conclusion: There is a low prevalence of drug-resistance-associated mutations in the isolated strains. Protease inhibitors in combination with reverse transcriptase inhibitors may be used to treat these patients in the future.